Intakes of folate, vitamin B6, and vitamin B12 and cardiovascular disease risk: a national population-based cross-sectional study - Huang, Jiamin; Khatun, Pipasha; Xiong, Yuqing; Liu, Bingrui; Zhao, Yisu; Lyu, Quanjun (Frontiers in Cardiovascular Medicine, 2023)
Background: Only a few studies that investigated dietary intakes of folate, vitamin B6, and vitamin B12 in relation to cardiovascular disease (CVD). This study aimed to assess the association of dietary folate, vitamin B6, and vitamin B12 with CVD in the United States population. Methods: A cross-sectional analysis of 65,322 adults aged ≥ 20 years who participated in the Third National Health and Nutrition Examination Survey (NHANES III) and NHANES 1999–2018. Before 2003, dietary intake data were assessed using a 24-hour dietary call, and two 24-hour dietary calls were used during 2003 and 2018. Odds ratios and 95% confidence intervals (CIs) for CVD associated with dietary folate, vitamin B6, and vitamin B12 were estimated using multivariate logistic regression models. Results Dietary vitamin B6 intake were inversely associated with the odds of CVD. In males, the multivariable OR for the highest versus lowest quartiles of vitamin B6 was 0.77 (95%CI: 0.61-0.97, Ptrend = 0.013) for the odds of CVD. In females, the adjusted OR for the highest quartile of vitamin B6 compared with the lowest quartile was 0.73 (95%CI: 0.56- 0.95, Ptrend = 0.038) for the odds of CVD. No significant association was observed between dietary folate and vitamin B12 intakes and the odds of CVD. Conclusions Our findings indicate that higher intake of dietary vitamin B6 may be associated with lower prevalence of CVD, suggesting that dietary vitamin B6 has major public health implications in the prevention of CVD in the United States population.